2015
DOI: 10.1016/j.mseb.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Improved p–n heterojunction device performance induced by irradiation in amorphous boron carbide films

Abstract: Amorphous hydrogenated boron carbide films (a-B 10 C 2+x :H y) on Si p-n heterojunctions were fabricated utilizing plasma enhanced chemical vapor deposition (PECVD). These

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The ultimate goal is an efficient, compact, low power detector relatively unaffected by terrestrial temperature changes. As an example, icosahedral semiconducting boron carbides [2][3][4][5][6] have recently garnered interest because they meet many of the operational requirements, but they still need significant neutron moderation to be efficient in detecting neutrons from fissile materials.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal is an efficient, compact, low power detector relatively unaffected by terrestrial temperature changes. As an example, icosahedral semiconducting boron carbides [2][3][4][5][6] have recently garnered interest because they meet many of the operational requirements, but they still need significant neutron moderation to be efficient in detecting neutrons from fissile materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Recent work has shown that neutron detectors and neutron voltaic devices, based on semiconducting boron carbides, may improve with some radiation exposure and are robust against radiation induced device degradation and failure. 14 The main causes for the poor neutron detection device performance are as follows: the insufficiently thick depletion region of the device, the need for a thicker device to come closer to neutron opacity, 1 and the need for better charge collection while maintaining low reverse bias leakage currents. Improvements in both charge collection and reverse bias leakage currents have been seen in plasma-enhanced chemical vapor (PECVD) semiconducting boron carbide based on composites (3:1) of pyridine and orthocarborane and attributed to the increase in hole carrier lifetimes to $350 ls compared to values of 35 ls for the PECVD semiconducting boron carbide films fabricated without pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, many works have been done and the results of which are regularly published in periodical scientific and scientific and technical journals. A large number of works are devoted to improve the technology of manufacturing solar cells (SC), a number of works notify about the introduced impurities in the structure of the initial materials [1] [2] [3] [4], and there are certain positive results on combining solar cells with thermoelectric converters (TEC) [5] [6]. In addition, there are many publications on the creation of heterojunction and cascade (SC)s; it is impossible to enumerate everything.…”
Section: Introductionmentioning
confidence: 99%